Biuletyn Informacyjny . 23 July 1981 (Wydanie Specjalne) - KZ NSZZ "Solidarność" HCP, [ed. Wiesława Chomicz, Bogdan Ciszak] (NSZZ "Solidarność" HCP, 1981)
Creation and circulation: For organizational use